G245(P) The impact of a dedicated youth worker in a paediatric accident and emergency. (27th April 2016) - Potter, S; Phillips, R; Hannon, F; Leith, E; Taylor, C; Hann, G
Abstract : Aims: Due to rising numbers of young people attending accident and emergency (A&E) due to youth-on-youth violence, an urban teaching hospital partnered with a local youth support charity in 2010. There is a clear need for similar support at this busy urban district general hospital. A parallel project was created in October 2014, to engage and support young people living in the local borough attending A&E due to violence and aggression. Method: 12 to 24 year olds are eligible for referral to our local youth worker, who was funded by a local neighbouring borough council. The referral is made after consent from the young person and them filling out a form, placed in boxes in the A&E department, paediatric assessment unit, paediatric inpatient ward and medical admissions unit. Young people receive dedicated one-to-one support from a youth worker; they receive a number of sessions to explore the reasons for their referral. There is scope to highlight personal aims and link them with relevant youth services. Results: Many of those who declined support were already engaging with the youth offending services or school counsellors. "I've realised that there's no point fighting for peace. If you want peace, you have to be peaceful" Ali, aged 16. Ali, with the help of his youth worker, talked in depth about the fight which caused his hospital presentation. He has received funding for a dance class he wanted to attend. The support Ali received is an example of the kind of help that all those involved have received. Conclusion: The project has successfully engaged young people attending A&E secondary to aggression and violence. A new partnership with a sister borough and funding from the local mayor has secured a second youth worker, offering more support to the vulnerable young people whose lives can be turned around.